Effects of piezo-viscous dependency on squeeze film between circular plates: couple stress fluid model - Singh, U. P. (My University, 2014)
In high pressure fluid flows applications such as fluid film lubrication, microfluidics and geophysics, the piezoviscous effect i.e. viscosity-pressure dependence plays an important role. In the present theoretical investigation, the combined effects of piezo-viscous dependency and non-Newtonian couple stresses on the performance of circular plate squeeze film bearings have been investigated using Stokes Micro-continuum theory of couple stress fluids together with the exponential variation of viscosity with pressure. Analytic solution for film pressure is obtained using small perturbation analysis. The numerical results for pressure and load capacity with different values of viscosity-pressure parameter are calculated and compared with iso-viscous couple stress and Newtonian lubricants. Due to piezo-viscous effect, enhanced pressure, increased load capacity and longer response time is observed in the analysis.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Couple stress fluids; Load-carrying capacity; Piezo-viscous effect; Squeeze-film lubrication; Viscosity-pressure